Paclitaxel-induced acute myocardial infarction: a case report and literature review - Gi Eun Kim (18185908) (2024)
Background Paclitaxel is a chemotherapeutic agent commonly used for ovarian, lung, breast carcinoma, and Kaposi’s sarcoma. Its common side effects include hypersensitivity reaction, bone marrow suppression, and peripheral neuropathy. However, a rare and life-threatening side effect is paclitaxel-induced myocardial infarction. Case presentation A 71-year-old man with type 2 diabetes mellitus, hypertension, heavy smoking history, previous coronary artery disease with percutaneous coronary intervention (PCI) in left anterior descending artery (LAD), and non-small lung cancer presented with non-ST elevation myocardial infarction during infusion of paclitaxel infusion. Coronary angiogram showed de novo three vessel disease with 70% stenosis in ostial to distal left main artery (LM) and 80% in-stent re-stenosis in proximal to mid left anterior descending artery. Conclusions Physicians should be keeping this in mind when dealing with patients on paclitaxel, especially if they have previous risk factors for coronary artery disease. Other Information Published in: BMC Cardiovascular Disorders License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12872-024-03814-1